Preparation method and application of pulsed electric field induced high-thermal-conductivity epoxy composite material
By using pulse electric field induction technology in epoxy resin, hexagonal boron nitride is oriented, and an efficient thermal conductivity path is constructed, which solves the problem of insufficient improvement of thermal conductivity of epoxy resin-based composite materials under low filling amount, and achieves high thermal conductivity and insulation It takes into account both mechanical properties and is suitable for the stable operation of large generators.
Patent Information
- Application Number
- CN202411694423.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to effectively improve the thermal conductivity of epoxy resin-based composite materials under low filling amounts, resulting in untimely heat release of the generator during operation, affecting the stable operation of the equipment.
Using pulse electric field induction technology, hexagonal boron nitride is oriented in epoxy resin as a filler. Through the induction of pulse electric field, the overlap probability between the fillers is increased and an efficient thermal conduction path is constructed.
It significantly improves the thermal conductivity of epoxy resin-based composite materials at low filling amounts, improves the thermal conductivity of the material, while maintaining insulation and mechanical properties. It is suitable for the high voltage, large capacity and miniaturization development of large generators.
Smart Images

Figure CN119490684A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resin composite material preparation, and in particular to a preparation method and application of a pulse electric field induced high thermal conductivity epoxy-based composite material. Background Art
[0002] Epoxy resin is widely used as the main insulation material of large generators due to its excellent insulation, mechanical and thermal stability. However, researchers have found that the thermal conductivity of epoxy resin is very low, which makes it impossible to quickly release the heat generated by the generator during operation. The large amount of heat accumulated inside the equipment seriously affects its stable operation. At present, the method of doping with inorganic high thermal conductivity fillers is commonly used in engineering to improve the thermal conductivity of epoxy resin-based composite materials. The direct doping method cannot prepare high thermal conductivity composite materials at low filling amounts, and a very high filling amount is required to achieve the desired effect. This is because only when the filler content is sufficient can the overlap between each other be achieved to build a complete thermal conductivity path, but at this time the insulation and mechanical properties of the material often undergo significant degradation.
[0003] Therefore, the research and preparation of a high thermal conductivity epoxy resin-based composite material with a low filling amount is of great practical significance for achieving stable operation of large generators and adapting to their development trend of high voltage, large capacity and miniaturization. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the thermal conductivity of epoxy resin-based composite materials is not significantly improved under low filling amount, and to provide a preparation method and application of a pulse electric field induced high thermal conductivity epoxy-based composite material.
[0005] A method for preparing a pulse electric field-induced high thermal conductivity epoxy-based composite material is carried out according to the following steps:
[0006] Step S1:
[0007] The epoxy resin and the curing agent methyl hexahydrophthalic anhydride are fully mixed, and then hexagonal boron nitride is added, and after ultrasonic dispersion, an accelerator 2,4,6-tris(dimethylaminomethyl)phenol is added to obtain a suspension;
[0008] The mass ratio of the epoxy resin to hexagonal boron nitride is 20:4.11;
[0009] Step S2:
[0010] The suspension obtained in step S1 is poured into a mold, and a pulsed square wave voltage of 0.001 Hz to 50 Hz and 50 V / mm to 200 V / mm is applied to both sides of the mold. The mold is then placed in a blast oven for gradient temperature curing to obtain a pulsed electric field induced high thermal conductivity epoxy-based composite material.
[0011] The invention discloses an application of a pulse electric field induced high thermal conductivity epoxy-based composite material, and the application of the pulse electric field induced high thermal conductivity epoxy-based composite material in a large generator.
[0012] Beneficial effects of the present invention:
[0013] (1) The present invention discloses a method for preparing a high thermal conductivity epoxy-based composite material induced by a pulse electric field. The method uses E51 epoxy resin as a matrix, non-zero-dimensional h-BN as a filler, and uses a pulse electric field to induce h-BN to orient in the epoxy resin matrix. The epoxy resin is then cured to retain the oriented structure. Compared with the blindness of directly doping the thermal conductive path, the present invention uses the induction effect of the pulse electric field to make h-BN face a specific direction, increasing the probability of mutual overlap, thereby promoting the construction of the thermal conductive path and solving the problem that the thermal conductivity of the epoxy resin-based composite material is not significantly improved at a low filling amount.
[0014] (2) The epoxy resin-based composite material prepared by the present invention has a significantly improved thermal conductivity compared to the composite material directly doped at the same filling amount. At the same time, the thermal conductivity of the epoxy resin-based composite material is significantly improved at a low filling amount by utilizing the induction effect of the pulsed electric field, which provides a new idea for the development of epoxy resin-based composite materials that integrate thermal conductivity, insulation and mechanical properties, and is of great significance for the development of high voltage, large capacity and miniaturization of large generators.
[0015] The invention can obtain a preparation method and application of a pulse electric field-induced high thermal conductivity epoxy-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A graph showing the thermal conductivity of the h-BN / EP composite material obtained by inducing a 50 Hz pulse square wave in Example 1;
[0017] Figure 2 A graph showing the thermal conductivity of the h-BN / EP composite material obtained by inducing a 0.1 Hz pulse square wave in Example 1;
[0018] Figure 3 The thermal conductivity effect diagram of the h-BN / EP composite material obtained by inducing a 0.001 Hz pulse square wave in Example 1 is shown. DETAILED DESCRIPTION
[0019] Specific implementation method 1: This implementation method is a method for preparing a high thermal conductivity epoxy-based composite material induced by a pulse electric field, which is carried out according to the following steps:
[0020] Step S1:
[0021] The epoxy resin and the curing agent methyl hexahydrophthalic anhydride are fully mixed, and then hexagonal boron nitride is added, and after ultrasonic dispersion, an accelerator 2,4,6-tris(dimethylaminomethyl)phenol is added to obtain a suspension;
[0022] The mass ratio of the epoxy resin to hexagonal boron nitride is 20:4.11;
[0023] Step S2:
[0024] The suspension obtained in step S1 is poured into a mold, and a pulsed square wave voltage of 0.001 Hz to 50 Hz and 50 V / mm to 200 V / mm is applied to both sides of the mold. The mold is then placed in a blast oven for gradient temperature curing to obtain a pulsed electric field induced high thermal conductivity epoxy-based composite material.
[0025] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the mass ratio of the epoxy resin, methylhexahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol described in step S1 is 20:17:0.06, and the epoxy resin is E51 epoxy resin.
[0026] The other steps are the same as those in the first specific implementation.
[0027] Specific embodiment 3: The difference between this embodiment and specific embodiment 1 or 2 is that in step S1, after the epoxy resin and the curing agent methylhexahydrophthalic anhydride are mixed, a power agitator is used to stir at a temperature of 60 to 70° C. for 20 to 30 minutes.
[0028] The other steps are the same as those in the first or second embodiment.
[0029] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that in step S1, the epoxy resin is preheated in an oven at 60 to 70°C for 20 to 30 minutes before use.
[0030] The other steps are the same as those in Specific Embodiments 1 to 3.
[0031] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that the ultrasonic dispersion time in step S1 is 2 to 3 hours.
[0032] The other steps are the same as those in Specific Embodiments 1 to 4.
[0033] Specific implementation example 6: This implementation example differs from specific implementation examples 1 to 5 in that the thickness d of the hexagonal boron nitride in step S1 is ≤ 100 nm, the inner diameter of the sheet is 1 to 3 μm, and the mass fraction of the hexagonal boron nitride in the high thermal conductivity epoxy-based composite material is 10%.
[0034] The other steps are the same as those in Specific Embodiments 1 to 5.
[0035] Specific implementation method 7: The difference between this implementation method and specific implementation methods 1 to 6 is that the duration of the pulse square wave voltage in step S2 is 60 minutes or 120 minutes.
[0036] The other steps are the same as those in Specific Embodiments 1 to 6.
[0037] Specific embodiment eight: The difference between this embodiment and specific embodiments one to seven is that in step S2, the pulse square wave voltage waveform is output by the waveform generator and applied to both sides of the mold via the high-voltage amplifier.
[0038] The other steps are the same as those in Specific Embodiments 1 to 7.
[0039] Specific embodiment nine: The difference between this embodiment and specific embodiments one to eight is: the gradient temperature rise curing described in step S2: first heat to 80°C and cure at 80°C for 2 to 3 hours; then heat to 100°C and continue to cure at 100°C for 2 to 3 hours; finally heat to 120°C and cure at 120°C for another 4 to 5 hours.
[0040] The other steps are the same as those in Specific Embodiments 1 to 8.
[0041] Specific implementation method ten: This implementation method is an application of a pulse electric field induced high thermal conductivity epoxy-based composite material, and the application of the pulse electric field induced high thermal conductivity epoxy-based composite material in a large generator.
[0042] The following examples are used to verify the beneficial effects of the present invention:
[0043] Example 1: A method for preparing a pulse electric field-induced high thermal conductivity epoxy-based composite material, comprising the following steps:
[0044] Step S1:
[0045] First, 20 g of E51 epoxy resin (EP) was preheated in an oven at 60°C for 30 min, and then 17 g of curing agent methyl hexahydrophthalic anhydride (MHHPA) was added thereto, and stirred at 60°C for 20 min using a power agitator, and then 4.11 g of hexagonal boron nitride (h-BN) was added. After ultrasonic dispersion for 2 h, 0.06 g of accelerator 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) was slowly dropped into the mixture using a syringe to obtain a suspension;
[0046] The thickness of the hexagonal boron nitride is d≤100nm, the inner diameter of the sheet is 1-3μm, and the mass fraction of the hexagonal boron nitride in the high thermal conductivity epoxy-based composite material is 10%;
[0047] Step S2:
[0048] The suspension was poured into a mold with a thickness of 4 mm. An arbitrary waveform generator (AFG3200C) output a pulsed square wave voltage with a frequency of 50 Hz. The voltage was amplified by a high-voltage amplifier (Model30 / 20A) and applied to both sides of the mold. The pulsed square wave electric field strength in the material was 50 V / mm, 100 V / mm, 150 V / mm and 200 V / mm, respectively, and the application time was 60 min and 120 min.
[0049] Step S3:
[0050] The pulse voltage was disconnected, and the mold was placed in a blast oven, first heated to 80°C and cured at 80°C for 2 hours; then heated to 100°C and continued to cure at 100°C for 2 hours; finally heated to 120°C and cured at 120°C for another 4 hours to obtain a pulse electric field induced high thermal conductivity epoxy-based composite material (h-BN / EP).
[0051] The thermal conductivity of the h-BN / EP composite material obtained under the conditions of this embodiment is measured and is shown in Table 1.
[0052] Table 1
[0053]
[0054] Embodiment 2:
[0055] The frequency of the pulsed square wave voltage in this embodiment is 0.1 Hz, and other experimental conditions are the same as those in Example 1. The thermal conductivity of the h-BN / EP composite material obtained under the conditions of this embodiment is shown in Table 2.
[0056] Table 2
[0057]
[0058] Embodiment 3:
[0059] The frequency of the pulsed square wave voltage in this embodiment is 0.001 Hz, and other experimental conditions are the same as those in Example 1. The thermal conductivity of the h-BN / EP composite material obtained under the conditions of this embodiment is shown in Table 3.
[0060] Table 3
[0061]
[0062] Comparative Example 1:
[0063] (1) 20 g of E51 epoxy resin was placed in an oven set at 60° C. and preheated for 30 min. Then, 17 g of MHHPA was added thereto and the mixture was stirred at 60° C. for 20 min using a force-enhancing stirrer. Then, 4.11 g of h-BN was added to the mixture and ultrasonically dispersed for 2 h. While keeping the above conditions unchanged, 0.06 g of DMP-30 was slowly dripped into the mixture using a syringe to prepare a suspension.
[0064] (2) pouring the obtained suspension into a mold with a thickness of 4 mm;
[0065] (3) The mold is placed in a blast oven and the epoxy resin is cured by gradient temperature increase. The curing conditions are 80°C for 2 h, 100°C for 2 h, and 120°C for 4 h to finally obtain the h-BN / EP composite material.
[0066] It was determined that the thermal conductivity of the h-BN / EP composite material obtained under the conditions of this comparative example was 0.234 W / (m·K).
[0067] Figure 1 The thermal conductivity effect diagram of the h-BN / EP composite material obtained by 50Hz pulse square wave induction in Example 1 is shown; Figure 1 As shown in the figure, the thermal conductivity of the samples applied with a 50Hz pulsed square wave electric field for 60min and 120min increases with the increase of the electric field strength, and is greater than the thermal conductivity of the comparative sample, but the thermal conductivity of the samples applied with the electric field for 60min and 120min is not much different. At the same time, the thermal conductivity and intensity ratio of the samples applied with a 50Hz pulsed square wave electric field at an applied field strength of 50V / mm for 60min and 120min show a certain difference, which indicates that the induced orientation effect of the 50V / mm pulsed square wave electric field on h-BN is not obvious when applied for 60min.
[0068] Figure 2 The thermal conductivity effect diagram of the h-BN / EP composite material obtained by 0.1 Hz pulse square wave induction in Example 1 is shown; Figure 2As shown in the figure, similar to 50Hz, the thermal conductivity of the samples applied with a 0.1Hz pulsed square wave electric field for 60min and 120min both showed an increase with the increase of the electric field intensity, and both were greater than the thermal conductivity of the sample in Comparative Example 1. Unlike the 50Hz samples, in this group of samples, there was almost no difference in the thermal conductivity of the 50V / mm samples after applying for 60min and 120min, which indicates that under the low frequency condition of 0.1Hz, the 50V / mm pulsed square wave electric field had almost no effect on the thermal conductivity of the composite material regardless of whether it was applied for 60min or 120min.
[0069] Figure 3 The thermal conductivity effect diagram of the h-BN / EP composite material obtained by 0.001 Hz pulse square wave induction in Example 1 is shown; Figure 3 As shown in the figure, the thermal conductivity of the samples applied with a 0.001Hz pulsed square wave electric field for 60min and 120min also showed the characteristic of increasing with the increase of the electric field strength, and both were much greater than the thermal conductivity of the comparative sample. Similar to the samples applied with a 0.1Hz pulsed square wave electric field, the samples induced by a 50V / mm pulsed square wave electric field did not show a large difference in thermal conductivity between the samples applied for 60min and 120min, further confirming the conclusion that the low-frequency pulsed square wave electric field at an electric field strength of 50V / mm is sufficient to cause the h-BN in the h-BN / EP composite material to respond and deflect.
Claims
1. A method for preparing a high thermal conductivity epoxy composite material induced by a pulse electric field, characterized in that The preparation method is carried out according to the following steps: Step S1: The epoxy resin and the curing agent methyl hexahydrophthalic anhydride are fully mixed, and then hexagonal boron nitride is added, and after ultrasonic dispersion, an accelerator 2,4,6-tris(dimethylaminomethyl)phenol is added to obtain a suspension; The mass ratio of the epoxy resin to hexagonal boron nitride is 20:4.11; Step S2: The suspension obtained in step S1 is poured into a mold, and a pulsed square wave voltage of 0.001 Hz to 50 Hz and 50 V / mm to 200 V / mm is applied to both sides of the mold. The mold is then placed in a blast oven for gradient temperature curing to obtain a pulsed electric field induced high thermal conductivity epoxy-based composite material.
2. The method for preparing a pulse electric field induced high thermal conductivity epoxy-based composite material according to claim 1, characterized in that The mass ratio of the epoxy resin, methylhexahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol in step S1 is 20:17:0.06, and the epoxy resin is E51 epoxy resin.
3. The method for preparing a pulse electric field induced high thermal conductivity epoxy-based composite material according to claim 1 or 2, characterized in that In step S1, the epoxy resin and the curing agent methylhexahydrophthalic anhydride are mixed, and then stirred at a temperature of 60 to 70° C. using a power agitator for 20 to 30 minutes.
4. The method for preparing a pulse electric field induced high thermal conductivity epoxy-based composite material according to claim 1 or 2, characterized in that In step S1, the epoxy resin is preheated in an oven at 60 to 70° C. for 20 to 30 minutes before use.
5. The method for preparing a pulse electric field induced high thermal conductivity epoxy-based composite material according to claim 1, characterized in that The ultrasonic dispersion time in step S1 is 2 to 3 hours.
6. The method for preparing a pulse electric field induced high thermal conductivity epoxy-based composite material according to claim 1, characterized in that The thickness of the hexagonal boron nitride in step S1 is d≤100 nm, the inner diameter of the sheet is 1-3 μm, and the mass fraction of the hexagonal boron nitride in the high thermal conductivity epoxy-based composite material is 10%.
7. The method for preparing a pulse electric field induced high thermal conductivity epoxy-based composite material according to claim 1, characterized in that The duration of the pulse square wave voltage in step S2 is 60 minutes or 120 minutes.
8. The method for preparing a pulse electric field induced high thermal conductivity epoxy-based composite material according to claim 1 or 7, characterized in that In step S2, a pulsed square wave voltage waveform is output by a waveform generator and applied to both sides of the mold via a high voltage amplifier.
9. The method for preparing a pulse electric field induced high thermal conductivity epoxy-based composite material according to claim 1, characterized in that The gradient temperature curing described in step S2 is: firstly heating to 80°C and curing at 80°C for 2-3h; then heating to 100°C and continuing curing at 100°C for 2-3h; finally heating to 120°C and curing at 120°C for another 4-5h.
10. Use of a pulse electric field induced high thermal conductivity epoxy composite material prepared by the method according to any one of claims 1 to 9, characterized in that The application of the pulse electric field induced high thermal conductivity epoxy-based composite material in large generators.
Citation Information
Cited By
Heat-conducting wear-resistant organic silicon composite resin and preparation method thereof
CN119912815A
High-thermal-conductivity epoxy composite material efficiently induced and oriented by high-frequency high-voltage bipolar square wave electric field and preparation method of high-thermal-conductivity epoxy composite material
CN120648166A
High-frequency high-voltage bipolar square wave electric field induced orientation high-thermal-conductivity epoxy composite material and preparation method thereof
CN120648166B